Effects of Digital Technologies on Older People's Access to Health and Social Care: Umbrella Review - Tafadzwa Patience Kunonga; Gemma Frances Spiers; Fiona R Beyer; Barbara Hanratty; Elisabeth Boulton; Alex Hall; Peter Bower; Chris Todd; Dawn Craig (JMIR Publications, 2021)
BackgroundThe 2020 COVID-19 pandemic prompted the rapid implementation of new and existing digital technologies to facilitate access to health and care services during physical distancing. Older people may be disadvantaged in that regard if they are unable to use or have access to smartphones, tablets, computers, or other technologies. ObjectiveIn this study, we synthesized evidence on the impact of digital technologies on older adults' access to health and social services. MethodsWe conducted an umbrella review of systematic reviews published from January 2000 to October 2019 using comprehensive searches of 6 databases. We looked for reviews in a population of adults aged ≥65 years in any setting, reporting outcomes related to the impact of technologies on access to health and social care services. ResultsA total of 7 systematic reviews met the inclusion criteria, providing data from 77 randomized controlled trials and 50 observational studies. All of them synthesized findings from low-quality primary studies, 2 of which used robust review methods. Most of the reviews focused on digital technologies to facilitate remote delivery of care, including consultations and therapy. No studies examined technologies used for first contact access to care, such as online appointment scheduling. Overall, we found no reviews of technology to facilitate first contact access to health and social care such as online appointment booking systems for older populations. ConclusionsThe impact of digital technologies on equitable access to services for older people is unclear. Research is urgently needed in order to understand the positive and negative consequences of digital technologies on health care access and to identify the groups most vulnerable to exclusion.